Stranger Fictions - Johnson, Rebecca C. (Cornell University Press, 2021)
Widely cited as the first Arabic novel, Zaynab appeared in 1913. Yet over the previous eight decades, hundreds of novels translated into Arabic from English and French were published, creating a vast literary corpus that influenced generations of writers across the Arabic world but that has, until now, been considered only as a curious footnote in the genre's history. In Stranger Fictions, Rebecca C. Johnson offers a transformative new account of modern Arabic literature by incorporating these works into the history the Arabic novel. Considering the wide range of nineteenth- and early twentieth-century translation practices—including
10.1515/9781501753305